Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.ppat.1005444
|View full text |Cite|
|
Sign up to set email alerts
|

Leader-Containing Uncapped Viral Transcript Activates RIG-I in Antiviral Stress Granules

Abstract: RIG-I triggers antiviral responses by recognizing viral RNA (vRNA) in the cytoplasm. However, the spatio-temporal dynamics of vRNA sensing and signal transduction remain elusive. We investigated the time course of events in cells infected with Newcastle disease virus (NDV), a non-segmented negative-strand RNA virus. RIG-I was recruited to viral replication complexes (vRC) and triggered minimal primary type I interferon (IFN) production. RIG-I subsequently localized to antiviral stress granules (avSG) induced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
88
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 48 publications
(51 reference statements)
10
88
2
Order By: Relevance
“…Rather than being inert structures, recent reports suggest SGs have antiviral properties; the granules concentrate and promote interactions between a number of innate immune activators, their downstream interferon-stimulated genes (RIG-I, PKR, MDA5, and OAS), and their targets (5,41,43). For example, pattern recognition receptors like RIG-I are activated upon binding to viral RNAs in SGs, which leads to the stimulation of interferon-related genes (42,43,82). Alternatively, recent studies suggest that in the absence of virus infection, SGs can activate innate immune signaling (11,83,84).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than being inert structures, recent reports suggest SGs have antiviral properties; the granules concentrate and promote interactions between a number of innate immune activators, their downstream interferon-stimulated genes (RIG-I, PKR, MDA5, and OAS), and their targets (5,41,43). For example, pattern recognition receptors like RIG-I are activated upon binding to viral RNAs in SGs, which leads to the stimulation of interferon-related genes (42,43,82). Alternatively, recent studies suggest that in the absence of virus infection, SGs can activate innate immune signaling (11,83,84).…”
Section: Discussionmentioning
confidence: 99%
“…GQ849007.1), and found that it contains 5′ppp and 3′poly(A + ). This RNA and the viral replication complex was shown to actually colocalize in cytoplasmic antiviral stress granules along with cellular RIG-I [53]. Similar IFN-inducing read-through RNA species were also confirmed in two other NNR viruses, namely vesicular stomatitis virus (Le-N) and RSV (Le-NS1).…”
Section: Evaluation Of Nnr Viral Rnas As a Potential Rig-i Ligandmentioning
confidence: 76%
“…The most recent hunt for RIG-I ligands have implicated the NNR viral LeRT transcript [53]. Specifically, a fraction of the LeRNA that reads through its transcription termination site into the next gene, generating what we will call ‘Leader-read-through' or LeRT RNA, was shown to be a major inducer of IFN via RIG-I [53].…”
Section: Evaluation Of Nnr Viral Rnas As a Potential Rig-i Ligandmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to bear in mind that SGs are being increasingly viewed as more than a mere consequence of a cell's stress response or a temporary storage depot for mRNPs. Two independent research groups have shown that SGs can promote innate immune responses (76)(77)(78)(79). This has led to the proposal that SGs serve as platforms for recognizing and responding to viral infections (80), which may explain why so many viruses destroy or modify SGs during infection and necessitates a better understanding of SG biology.…”
Section: Discussionmentioning
confidence: 99%